Ex Uno Lapide: The making present of absence - Buhagiar, Konrad; Dreyfuss, Guillaume; Joris, Ephraim (Interstices: Journal of Architecture and Related Arts, 2019)
This paper comments on a drawing protocol entitled the “Monolith Drawing”, with which an architectural figure is extracted out of a single volume, synchronising analogue thinking with computational development, to enter history through our capacity to long for the experience of something that is absent. The Lacanian interpretation assumes there cannot be absence in an objective world, for absence can only exist through symbolic or representative means. It is through the representational means of the Monolith Drawing that we enable ourselves, as architects, to design presence where there is none. This research explores and (re)deploys the notion of ex uno lapide in contemporary architectural production. Such creative practice recovers a tradition linking geology with architectonic drawing and operates in conceptual space through means of contained sets of formal operations to generate a particular kind of architecture. The Monolith Drawing is here explained in relation to the design of a museum extension to house a tapestry cycle by Peter Paul Rubens, adjacent to St John’s Co-Cathedral in Valletta. These tapestries represent the idea of transubstantiation. In response, the museum’s design acts as a closed vessel, a monumental reliquary, enabling a closed and controlled environment to ensure the conservation of the artwork. The reliquary is interpreted as a container of meaning, directing a reciprocal gaze towards the idea of meaningful absence. The Monolith Drawing installs two important principles. The idea of the mirror-construct, in which an object is depicted using parallel lines to project its mirror image and allow twofold vision, outwards (res extensa) and inwards (res cogitans); and the idea of ex uno lapide – a strategy where architecture is carved out of solid mass. This carving is guided by allowing the depicted object and its mirror image to intersect. Its transcriptions allow for a drawing with history; a tracing of its own tracing.